Аналитический метод расчета магнитного поля и моментов электродвигателя с постоянными магнитами дискового типа - Гребеников, В.В.; Гамалия, Р.Р. (Технічна електродинаміка, 2012)
We consider an analytical method for calculating the magnetic field of disk-type motor with a transverse magnetization of permanent magnets located on the rotor. An analytical solution of 2-D Laplace problem for the vector magnetic potential in the area of the pole pitch for the cross section of the disc-type motor magnetic system by the average radius is given. The results of calculation of the magnetic field induction in the gap between the rotor and stator, and the dependence of torque on the rotor position relative to the stator are shown. The results are compared with the numerical solution of the problem in the package Elcut 5.6.